ANALISIS KECANDUAN SMARTPHONE PADA MAHASISWA MENGGUNAKAN METODE K-NEARST NEIGHBORS (K-NN) - Ivana Dwikartika Sari; Zaehol Fatah (CV. Denasya Smart Publisher, 2024)
Smartphone are a tecnology that is widely used among teenagers. Smartphone have a negative impact on teenagers, one of which is that amsrtphone addiction can interfere with various activities in teenagers’ real lives.this writing aims to understand and describe various aspects including health aspects, psychological aspects, academic aspects, social aspects and financial aspects. Classification is carried out to support decision making regarding smartphone addiction problems. K-Nearest Neighbors (KNN) is a machine learning classification method used in this research. The research results show that the best method for classifying smartphone addiction is KNN with attribute selection using Linear Regression based on weight correlation.